Study of doxorubicin release on apoferritin-magnetic-doxorubicin nanoparticle. Issue 1 (February 2021) - Prasetya, A D; Sulungbudi, G T; Wildan, Z L; Mujamilah,
Abstract: Conjugation of nanoparticle with some substance can be a solution to a theragnostic of cancer cells. The release of doxorubicin from conjugated apoferritin-magnetic-doxorubicin (APO-NPM-DOX) was studied in different pH conditions and incubation time. The preparation of magnetic nanoparticle (Fe3 O4 ) was done through the co-precipitation method using FeCl3 and FeCl2 (mol ratio 1:1) as the precursor. The encapsulation process was started by conjugation of magnetic nanoparticle with doxorubicin, then followed by incubation of the mixture in apoferritin solution for 2 hours in pH 3. The mixture was then set to pH 8 using NaOH and dialyzed in Tris-HCl. The doxorubicin release from APO-NPM-DOX was studied by incubation at 36.5 °C in different time variations in pH 5 and different pH conditions (4, 5, 6, 7) for a week. The doxorubicin release trend becomes steady after three days of incubation in pH 5 with 4.6% of the doxorubicin had been released. The highest percentage of doxorubicin release was found in pH 4, which is more than 1.2 times higher than in pH 5.